1984
DOI: 10.1104/pp.75.1.151
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Natural-Abundance 13C Nuclear Magnetic Resonance Studies of Living Ectomycorrhizal Fungi

Abstract: ABSTRACINatural-abundance '3C nuclear magnetic resonance spectoscopy has been used to study intact mycelia of the ectomycorrhizal fungi Cenococ-cur gmniforme (Ascomycetes) and Hebeloma crastliniforme (Basidiomycetes These results suggest that fatty acids droplets could be involved in carbon storage and metabolism from ectomycorrhizal fungi.Ectomycorrhizal fungi live in symbiotic association with the roots of the major part of woody species. The mycobiont stimulates greatly the phosphorus and nitrogen uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The spectral properties, including 1 H NMR and 13 C NMR data, were identical to those previously reported in the literature (Martin et al, 1984;Mahato & Kundu, 1994;De-Eknamkul & Potduang, 2003;Lima et al, 2004). Compounds 1 and 2 are oleanane triterpenes and compound 3 is friedooleanane triterpene.…”
Section: Compounds Isolationsupporting
confidence: 78%
“…The spectral properties, including 1 H NMR and 13 C NMR data, were identical to those previously reported in the literature (Martin et al, 1984;Mahato & Kundu, 1994;De-Eknamkul & Potduang, 2003;Lima et al, 2004). Compounds 1 and 2 are oleanane triterpenes and compound 3 is friedooleanane triterpene.…”
Section: Compounds Isolationsupporting
confidence: 78%
“…Most vascular plants, except for a few droughtresistant plants, are unable to produce trehalose (37). The presence of trehalose has been evidenced in all kinds of mycorrhizas, including vesicular and arbuscular endomycorrhizas (1,46), arbutoid endomycorrhizas or orchids (19), and ectomycorrhizas (21,33,39). Furthermore, trehalose is the most abundant carbohydrate accumulated in the mycelium of L. bicolor in pure culture (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated to be involved in the growth‐promoting effect of a MHB strain of Pseudomonas monteilii on the ectomycorrhizal fungus Pisolithus albus in a two‐compartment plate assay (Duponnois & Kisa, 2006): P. monteilii significantly increased fungal growth when cultivated on a minimal medium amended with trehalose, while none of the other seven organic compounds tested produced the same effect. Finally, we recently observed that the biofilm‐forming MHB strain P. fluorescens BBc6R8 is chemoattracted by trehalose as well as by the mycelium of L. bicolor (unpublished results), which was proved to accumulate trehalose in its hyphae (Martin et al ., 1984). Therefore, we can now hypothesize that fungal metabolites, such as trehalose, secreted from fungal cells, can facilitate the colonization of the hyphae and the formation of MHB biofilms on them.…”
Section: Ecological and Evolutionary Implications Of Mhbmentioning
confidence: 96%